Analysis of Barriers to Public and Private Cardiac Rehabilitation Programs in Patients with Low and High Adherence - Santos, Lorena Altafin [UNESP]; Pinheiro, Dyovana Gomes [UNESP]; da Silva, Jéssica Malek [UNESP]; Borges, Giovanna Lombardi Bonini [UNESP]; da Silva, Paula Fernanda [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Sociedade Brasileira de Cirurgia Cardiovascular, 2023)
Introduction: Participants in cardiac rehabilitation programs have low adherence to their sessions, which makes extremely important to recognize the barriers that cause non-adherence, identifying whether the type of service and level of adherence influence these barriers. Methods: This is a cross-sectional observational study, in which 220 individuals (66.80±11.59 years) of both genders who are members of public and private exercise-based cardiac rehabilitation programs participated. The volunteers were divided according to the level of adherence, considering patients with low adherence (PLA) those with < 70% of attendance and high adherence (PHA) those with > 70%. Then, initial evaluation, Cardiac Rehabilitation Barriers Scale, analysis of socioeconomic level, Hospital Anxiety and Depression Scale, and Mini-Mental State Examination were applied. Results: Higher total barriers were found in PLA in the public service compared to PHA in the private service (P=0.023). In the subscale “perceived need”, PHA in the public service showed higher values than PLA and PHA in the private service (P≤0.001). The “access” barrier was higher for PHA in the public service when compared to PHA in the private service (P=0.024). PHA in the public service exhibited a higher barrier regarding questions about distance, transportation problems, cost, and time constraints. Conclusion: The public program presents higher barriers in the questions and categories compared to the private program, mainly the PHA. Furthermore, there are differences in the profile of the participants regarding socioeconomic and anxiety levels, treatment time, ethnicity, and city where they live.
Keywords: Attitude of Health Personnel; Cardiac Rehabilitation; Cardiovascular Diseases; Choice Behavior; Health Services Accessibility; Patient Preference